High-Throughput Metabolomics Discovers Metabolic Biomarkers and Pathways to Evaluating the Efficacy and Exploring Potential Mechanisms of Osthole Against Osteoporosis Based on UPLC/Q-TOF-MS Coupled With Multivariate Data Analysis - Si, Zhenxing; Zhou, Shifeng; Shen, Zilong; Luan, Feiyu (Frontiers in Pharmacology, 2020)
Postmenopausal osteoporosis (PMOP) is a most common metabolic bone illness among the elderly especially in postmenopausal women resulting from a reduction in bone mineral density, but there is no effective drug at present. The study was aimed at evaluating efficacy of osthole against osteoporosis using high-throughput metabolomics method. The blood samples for illustrating the pathological mechanism of PMOP and exploring the efficacy of osthole treatment (ST) were collected to perform metabolites and metabolic profiles and pathways analysis using UPLC/Q-TOF-MS and pattern recognition methods. In addition, backbone weight, the bone density and some vital biochemical indexes were also detected. A total of twenty-eight metabolites were identified as biomarkers for ovariectomized-osteoporosis model, and ST could significantly regulate nineteen of them including lysine, linoleic acid, 3-hydroxybutyric acid, prostaglandin F2a, taurocholic acid, LysoPC(15:0), L-carnitine, glucose, arginine, citric acid, corticosterone, ornithine, tryptophan, arachidonic acid, Cer(d18:0/18:0), glutamine, uric acid, 8-HETE, estriol, which mainly related with thirteen metabolic pathways such as linoleic acid metabolism, starch and sucrose metabolism, arachidonic acid metabolism, alanine, aspartate and glutamate metabolism, arginine and proline metabolism, citrate cycle (TCA cycle) and arginine biosynthesis. The ovariectomized model (OVX)-rats displays a significant decrease bone density, TGF-β1, NO and NOS level, and a significant increase bone weight, IL-6, TNF-α, and Ca 2+ level. These parameters in the ST rats were evidently improved as compared to the OVX group. ST effectively mitigated ovariectomy-induced osteoporosis in rats by affecting endogenous metabolites related metabolic mechanism, and showed the natural alternative with potential for the treatment of PMOP.